Mitotic arrest of breast cancer MDA-MB-231 cells by a halogenated thieno[3, 2-d]pyrimidine. Issue 8 (15th April 2015) - Ross, Christina R.; Temburnikar, Kartik W.; Wilson, Gerald M.; Seley-Radtke, Katherine L.
Graphical abstract: Abstract: Halogenated thieno[3, 2- d ]pyrimidines exhibit antiproliferative activity against a variety of cancer cell models, such as the mouse lymphocytic leukemia cell line L1210 in which they induce apoptosis independent of cell cycle arrest. Here we assessed these activities on MDA-MB-231 cells, a well-established model of aggressive, metastatic breast cancer. While 2, 4-dichloro[3, 2- d ]pyrimidine was less toxic to MDA-MB-231 cells than previously observed in the L1210 model, flow cytometry analysis showed that MDA-MB-231 cell death involved arrest at the G2/M stage of the cell cycle. Conversely, the introduction of bromine at C7 of the 2, 4-dichloro[3, 2- d ]pyrimidine eliminated cell type-dependent differences in cytotoxicity or cell cycle status. Together, these data indicate that a substituent at C7 can profoundly modify the cytotoxic mechanism of halogenated thieno[3, 2- d ]pyrimidines in a cell type-specific manner.